Mister Max : The Book of Lost Things - Voigt, Cynthia; Bruno, Iacopo (New York : Alfred A. Knopf, 2013)
"When Max's parents leave the country without him, he must rely on his wits to get by, and before long he is running his own--rather unusual--business"--
Keywords: Self-reliance -- Juvenile fiction; Problem solving -- Juvenile fiction; Self-reliance -- Fiction; Problem solving -- Fiction